Duodenal Diverticulitis Accompanied by Portal Vein Thrombosis Treated with Endoscopic Therapy - SungHyeok Ryou; Kwangwoo Nam; Jinmo Kim (The Korean Journal of Gastroenterology, 2021)
A 44-year-old woman presented with right upper abdominal pain and nausea with a 4-day duration. An abdominopelvic CT scan revealed a 2.3-cm sized cystic lesion in the duodenum with inflammatory changes and partial thrombosis in the distal main portal vein. Empirical antibiotics were initiated considering acute duodenal diverticulitis, but the symptoms worsened. Side-viewing duodenoscopy revealed purulent fluid draining spontaneously from a small diverticular opening. After enlarging the opening using an extraction balloon, sweeping followed by saline irrigation was performed, and pus and food debris gushed out into the duodenal lumen. The patient recovered rapidly and was discharged uneventfully on the 5th day post-hospitalization with oral antibiotics and warfarin. A follow-up CT scan and duodenoscopy 1 month later revealed a normal-appearing duodenal diverticulum and complete resolution of the portal vein thrombosis. This paper reports a rare case of portal vein thrombosis associated with duodenal diverticulitis. Overall, endoscopic therapy can be effective when conservative management fails and might be a viable alternative to surgery for treating duodenal diverticulitis.